Caste and Community in the Novels of Mulk Raj Anand: A Critical Rereading of Untouchable and Coolie (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper undertakes a close critical rereading of caste and community in two of Mulk Raj Anand's early novels, Untouchable (1935) and Coolie (1936), read together as a diptych on the structural production of human waste under colonial modernity. Rather than treating caste and class as parallel or interchangeable systems of exclusion, the paper argues that Anand's fiction traces a specific historical hinge: the moment at which a ritual hierarchy of purity and pollution, inherited from pre-colonial social organisation, is absorbed into and partially reconfigured by an emerging colonial-capitalist economy of wage labour. Untouchable compresses this argument into the single day of Bakha, a young sweeper in the fictional cantonment town of Bulashah, whose body is marked as permanently polluting regardless of his conduct or intention; Coolie extends it across the itinerant, multi-year odyssey of Munoo, an orphaned hill boy whose successive employments in Sham Nagar, Daulatpur, Bombay and Simla show caste stigma mutating into, without ever being replaced by, the disposability of the unskilled worker. Drawing on close reading, postcolonial theory, and the historical record of colonial governmentality, the paper contends that Anand's much-discussed 'solutions'--conversion, Gandhian reform, and the machine, on the one hand, and trade-union solidarity, on the other--are staged not as answers but as unresolved provocations, and that this formal irresolution is itself the novels' most enduring political argument. The paper closes by situating this reading against more recent Dalit-critical scholarship that has questioned the adequacy of a non-Dalit, upper-caste author's authorial voice to represent Dalit interiority, arguing that Anand's fiction is best read today as a historically significant but structurally limited intervention rather than a final or sufficient account of caste.